Effects of pre-activated adipose derived mesenchymal stem cells on experimental equine fetlock osteoarthritis model - Monteiro, Susana (2016)
EFFECTS OF PRE-ACTIVATED ADIPOSE MESENCHYMAL STEM CELLS ON EXPERIMENTAL EQUINE FETLOCK OSTEOARTHRITIS MODEL. Monteiro S*1 , Maninchedda U2 , Roussignol G3 , Remandet B3 , Segard E2 , Hilairet S3 , Jorgensen C4 , Lepage OM*2 . 1 Departamento de Medicina Veterinaria, Escola de Ci^encias e Tecnologia, Instituto de Ci^encias Agrarias e Ambientais Mediterr^anicas, Instituto de InvestigacS~ao e FormacS~ao Avancada, Universidade de S Evora, Evora, Portugal, 2 University of Lyon; VetAgro Sup, Veterinary Campus of Lyon, GREMERES-ICE Lyon Equine Research Center, Marcy l Etoile, France, 3 Sanofi-aventis Recherche, Montpellier, France, 4 CHU Lapeyronie University Hospital, Montpellier, France. Introduction: Mesenchymal stem cells (MSCs) have reparative effects due to paracrine actions and need to be activated by inflammatory mediators. Therefore, pre-activation of MSCs could lead to a more efficient therapeutic activity than unstimulated MSCs. Our objective was to study the effects of interferon-g (INF-g) pre-activated or “primed” allogeneic MSC in experimental osteoarthritis models, in vitro and in vivo, in horses. Methods: Equine adipose derived mesenchymal stem cells (ASC) were characterized and activated with IFN-g. ASC were tested on equine cartilage explants subjected to interleukin-1 (IL-1) and oncostatine-M (n ¼ 8). The experimental in vivo model of OA was induced by arthroscopy, using an adapted “groove” technique in 1 distal metacarpal condyle. Group A (n ¼ 6) did not receive any treatment; Group B (n ¼ 6) received intra-articular injection of 15 million INF-g activated ASC in a vehicle (3 mL) and Group C (n ¼ 4) received the vehicle alone (3 ml), 7 days post-surgery. After 15 days stall-rest horses respected a standardized exercise protocol. They were clinically evaluated before surgery (d0), in the middle (d45) and in the end of the study (d75), using an inertial sensor device for objective lameness examinations, synovial fluid analysis and radiography. All articular surfaces were evaluated macroscopically and histologically. Results: In the experimental study in vitro, IL-1 and oncostatine-M treatment induced a significant (P <.001) increase in glycosaminoglycans (GAG) release to the culture medium. Cartilage explants treated with ASC showed less GAG degradation and IFN-g pre-activation enhanced the protective effect (P = .019). In vivo, there was no significant difference in mean head movement asymmetry and radiographic scores between groups throughout the study (P >.05). Estimated proportions of lame horses at the end of the study was 83%, 33% and 50% and mean radiographic score was 11.8, 7.7 and 9 in group A, B and C, respectively. There was no significant difference in synovial fluid TP and PGE2 mean values, nor in macroscopic and histologic mean scores between groups (P >.05). Discussion and conclusion: IFN-g primed allogeneic ASC treatment had benefic effects observed in vitro by significant reduced GAG production but these effects were less evident clinically. Perhaps there was not enough inflammation by the time of the treatment (d7) or maybe the number of stem cells was not adequate. This could be explained by insufficient number of cells for this type of joint or accelerated clearance of the cells from the joint environment. Using INF-g primed allogeneic ASC treatment has protective effect in vitro and should be further explored clinically before it can be recommended in acute osteoarthritis in horses.